Molecular mechanisms of acquired idiopathic generalized anhidrosis: differential gene expression and potential therapeutic targets - Sanjukta Dasgupta (Discover Applied Sciences)
Abstract Eccrine sweat glands are essential for thermoregulation. Acquired idiopathic generalized anhidrosis (AIGA) is a rare disorder characterized by the absence of sweating, leading to severe complications like heatstroke and skin dryness. The underlying etiology remains unknown, complicating diagnosis and treatment. This study aimed to elucidate the genetic mechanisms of AIGA by analysing the gene expression in eccrine sweat glands using the GSE193125 dataset from the NCBI Gene Expression Omnibus (GEO). This study identified differentially expressed genes (DEGs) (genes that show statistically significant differences in expression levels in AIGA), with JUN and CCN1 significantly downregulated in anhidrotic lesions of AIGA patients. Receiver operating characteristic (ROC) curve demonstrated the accuracy of these genes in classification (JUN = 0.88 and CCN1 = 0.77). Gene and protein interaction networks which are defined as networks of physical interactions between genes and proteins, constructed using GeneMANIA and STRING, revealed substantial physical interactions among them. Gene set enrichment analysis highlighted the neuroinflammatory and estrogen receptor signaling pathways are associated with this condition, suggesting hormonal regulation’s role in the anhidrosis mechanism. Key miRNAs, including hsa-let-7b-5p, hsa-miR-10b-5p, and hsa-miR-124-3p, are associated with the DEGs, underscoring the importance of post-transcriptional and transcriptional regulation. Through the Drug Gene Interaction Database (DGIdb), ciprofibrate is identified as a potential therapeutic agent targeting the JUN gene. Molecular docking confirmed a strong binding affinity between ciprofibrate and JUN, suggesting ciprofibrate could modulate JUN activity and regulate AIGA symptoms. ADMET analysis, which refers to the assessment of absorption, distribution, metabolism, excretion, and toxicity of a drug or compound, is crucial for evaluating its pharmacokinetic and safety profile. The analysis indicated that ciprofibrate has favourable pharmacokinetic properties and a relatively safe toxicity profile. This comprehensive bioinformatics approach, integrating gene expression analysis, miRNA identification, and drug interaction, provides valuable insights into anhidrosis molecular pathology and highlights ciprofibrate’s potential as a targeted therapeutic strategy. Despite limitations, including a small sample size and reliance on computational predictions, this study paves the way for further research and potential therapeutic interventions for AIGA.